Electro/magnetoencephalographic signatures of human brain insulin resistance. (June 2016) - Hege, Maike A; Kullmann, Stephanie; Heni, Martin; Schleger, Franziska; Linder, Katarzyna; Fritsche, Andreas; Preissl, Hubert
Highlights: Electro/magnetoencephalography allow the direct assessment of neuronal activity. Human brain insulin resistance alters brain activity. Human brain insulin resistance may already be programmed in utero . Abstract : Human insulin action influences eating behavior, peripheral metabolism and cognition. Detailed insights into the neuronal processes related to human brain insulin action can be obtained by direct measures of neuronal activity with electroencephalography and magnetoencephalography. Results of recent studies show that spontaneous, task and stimulus related neuronal activity is modulated by insulin and that several factors like increased body weight and body composition can result in brain insulin resistance. Recent technological advances even allow the investigation of human brain functions in utero in relation to the metabolic status of the mother and indicate an effect of the mother's insulin sensitivity on the brain function of the fetus. In conclusion, studies based on direct neuronal measurements may help to determine the developmental trajectory related to insulin action and resistance.